Rickettsia spp. in rodent-attached ticks in Estonia and first evidence of spotted fever group Rickettsia species Candidatus Rickettsia uralica in Europe - Maria Vikentjeva; Julia Geller; Jaanus Remm; Irina Golovljova (Parasites & Vectors, 2021)
Abstract Background Rickettsia spp. are human pathogens that cause a number of diseases and are transmitted by arthropods, such as ixodid ticks. Estonia is one of few regions where the distribution area of two medically important tick species, Ixodes persulcatus and I. ricinus, overlaps. The nidicolous rodent-associated Ixodes trianguliceps has also recently been shown to be present in Estonia. Although no data are available on human disease(s) caused by tick-borne Rickettsia spp. in Estonia, the presence of three Rickettsia species in non-nidicolous ticks has been previously reported. The aim of this study was to detect, identify and partially characterize Rickettsia species in nidicolous and non-nidicolous ticks attached to rodents in Estonia. Results Larvae and nymphs of I. ricinus (n = 1004), I. persulcatus (n = 75) and I. trianguliceps (n = 117), all removed from rodents and shrews caught in different parts of Estonia, were studied for the presence of Rickettsia spp. by nested PCR. Ticks were collected from 314 small animals of five species [Myodes glareolus (bank voles), Apodemus flavicollis (yellow necked mice), A. agrarius (striped field mice), Microtus subterranius (pine voles) and Sorex araneus (common shrews)]. Rickettsial DNA was detected in 8.7% (103/1186) of the studied ticks. In addition to identifying R. helvetica, which had been previously found in questing ticks, we report here the first time that the recently described I. trianguliceps-associated Candidatus Rickettsia uralica has been identified west of the Ural Mountains.